Clinical impact of urinary CD11b and CD163 on the renal outcomes of anti-neutrophil cytoplasmic antibody-associated glomerulonephritis. Issue 8 (8th July 2020) - Yokoe, Yuki; Tsuboi, Naotake; Imaizumi, Takahiro; Kitagawa, Akimitsu; Karasawa, Munetoshi; Ozeki, Takaya; Endo, Nobuhide; Sawa, Yuriko; Kato, Sawako; Katsuno, Takayuki; Maruyama, Shoichi; Yamagata, Kunihiro; et al.
Abstract: Background: The detection of leukocyte-derived CD11b (α subunit of integrin Mac-1) and CD163 (scavenger receptor) in urine may reflect renal inflammation in antineutrophil cytoplasmic antibody-associated glomerulonephritis (ANCA-GN). The objective of this study was to evaluate the clinical significance of urinary CD11b (U-CD11b) and CD163 (U-CD163) in ANCA-GN. Methods: U-CD11b and U-CD163 were examined using enzyme-linked immunosorbent assay in ANCA-GN urine samples from our institutional cohort ( n  = 88) and a nationwide cohort ( n  = 138), and their association with renal histology was subsequently analyzed. Logistic regression analyses were performed on a nationwide ANCA cohort to determine the associations of the two urinary molecules with renal remission failure at 6 months or with yearly estimated glomerular filtration rate (eGFR) slope over a 24-month observation period. Results: U-CD11b and U-CD163 were significantly associated with cellular crescent formation and leukocyte accumulation in glomerular crescents. With regard to interstitial inflammation, both levels of U-CD11b and U-CD163 at diagnosis remarkably increased in ANCA-GN compared with the levels observed in nonglomerular kidney disorders including nephrosclerosis, immunoglobulin G4-related disease and tubulointerstitial nephritis; however, the presence of U-CD11b alone was significantly correlated with tubulointerstitial leukocyte infiltrates. Although neither U-CD11b nor U-CD163 at diagnosis was associated with remission failure at 6 months, multivariate analysis demonstrated that the baseline U-CD11b levels were significantly associated with the increase in eGFR following immunosuppressive therapy. Conclusions: Although both U-CD11b and U-CD163 reflect renal leukocyte accumulation, U-CD11b at diagnosis provides additional clinical value by predicting the recovery rate after the treatment of ANCA-GN.